Athletic ability, performance, and character: A hierarchical examination of prospective college athlete evaluation and the function of recruiting as institutional work - Drew Swinney; Chris Corr; Sarah Stokowski; Mike Godfrey (Journal of Intercollegiate Sport, 2025)
Intercollegiate athletics recruiting is depicted by the National Collegiate Athletic Association (NCAA) as the “lifeblood” of college sport. Given the correlation between recruiting success and winning in college football specifically, and the relationship between winning and revenue generation, NCAA member institutions place the utmost significance on football recruiting. Within the context of football recruiting as strategic institutional work, college football coaches promulgate institutionalized logics through the indoctrination of prospective college athletes. To further conceptualize institutional work and logics in the recruitment of prospective college athletes, the present study sought to examine the evaluative factors college football coaches prioritize when recruiting prospective college athletes. Semi-structured interviews with 10 football coaches at Football Bowl Subdivision member institutions during the 2023 college football season reveal the strategic emphasis placed on football ability and football character in the recruitment of prospective college athletes.